Full-field dynamic strain reconstruction of rotor blades under multi-mode vibration. (30th September 2022) - Zhu, Yuda; Wang, Yanan; Qiao, Baijie; Fu, Shunguo; Liu, Meiru; Luo, Xianqiang; Chen, Xuefeng
Highlights: The full-field dynamic strain of rotating blades is reconstructed from a limited set of measured strain responses, whether single-mode or multi-mode vibration. The proposed method is validated by numerical simulations and spinning experiments on rotor blades. The results demonstrate the high consistency between the reconstructed and measured strain. The strain distribution is reconstructed under blade multi-mode vibration, which has the potential for real-time blade vibration monitoring and residual life evaluation. Abstract: The peak stress for the high-speed rotating blade is time-varying and space-varying under multi-mode vibration, which affects the measurement accuracy of dynamic strain. The full-field dynamic strain reconstruction method for high-speed rotating blades under multi-mode vibration is proposed based on limited measured strain data to ameliorate the strain-based reliability analysis. Firstly, the dynamic behavior of the high-speed rotating blade is analyzed by dynamic blade modeling to accomplish multi-mode blade finite element modeling and verification. Secondly, the transformation matrix between the limited measured strain data and the full-field dynamic strain is derived from the blade mode shape. Finally, the full-field dynamic strain of the high-speed rotating blade under multi-mode vibration is obtained by combining the limited set of measured strain data and the transformation matrix. Simulations and experiments demonstrate that the proposed method guarantees the accuracy of the full-field dynamic strain predictions for rotor blades under both single-mode and multi-mode vibrations.